2001
DOI: 10.1128/jvi.75.15.6800-6807.2001
|View full text |Cite
|
Sign up to set email alerts
|

Longer and Shorter Forms of Sendai Virus C Proteins Play Different Roles in Modulating the Cellular Antiviral Response

Abstract: The Sendai virus (SeV) C gene codes for a nested set of four C proteins that carry out several functions, including the modulation of viral RNA synthesis and countering of the cellular antiviral response. Using mutant C genes (and in particular a C gene with a deletion of six amino acids present only in the larger pair of C proteins) and recombinant SeV carrying these mutant C genes, we find that the nested set of C proteins carry out a nested set of functions. All of the C proteins interdict interferon (IFN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 44 publications
3
72
2
Order By: Relevance
“…In five serine residues which constitute the phosphoacceptors in the P protein of the CVS strain [13], Ser 210 and Ser 271 within the PKC phosphoacceptor target were notably conserved in all lyssavirus genotypes (GT 1 to 7) [32], including the Brazilian RV variants examined in this study. Studies on VSV and paramyxovirus have shown that P gene-encoded multiple proteins are important in the viral replication cycle and pathogenicity of the virus [12,24,37]. The four methionine residues located in-frame of single P protein sequences are translated into four proteins of various lengths with no known function in the CVS strain [4].…”
Section: Discussionmentioning
confidence: 99%
“…In five serine residues which constitute the phosphoacceptors in the P protein of the CVS strain [13], Ser 210 and Ser 271 within the PKC phosphoacceptor target were notably conserved in all lyssavirus genotypes (GT 1 to 7) [32], including the Brazilian RV variants examined in this study. Studies on VSV and paramyxovirus have shown that P gene-encoded multiple proteins are important in the viral replication cycle and pathogenicity of the virus [12,24,37]. The four methionine residues located in-frame of single P protein sequences are translated into four proteins of various lengths with no known function in the CVS strain [4].…”
Section: Discussionmentioning
confidence: 99%
“…77, 2003 STAT2 ACTIVATION PROCESS AS A TARGET OF SeV C PROTEIN 3367 also the shorter forms (Y1 and Y2) can inhibit IFN-␣ signaling (10,11); however, only the larger proteins prevent establishment of the IFN-mediated anti-vesicular stomatitis virus (VSV) state (10). In contrast, Kato et al have presented evidence for the equal activities of the longer and shorter C proteins for the inhibition of IFN-mediated anti-VSV state, as well as IFN signaling (22).…”
Section: Fig 8 Stat1mentioning
confidence: 99%
“…In addition to the C protein, the shorter forms, Y1 and Y2, have the ability to inhibit IFN signaling (11,22). The C protein, however, does not lead to degradation of any component on the signaling pathway in most cell types (12,18,24,42,49) except for NIH 3T3 mouse embryo fibroblast (MEF) cells (10,11). The purpose of the present study was to better understand how the SeV C protein inhibits IFN-␣ signaling without degrading cellular proteins on the signaling pathway.…”
mentioning
confidence: 99%
“…In particular, all four have been shown to interact with Stat1, an interaction that blocks type 1 interferon signaling to reporter genes carrying interferon-stimulated response elements. However, whereas binding to either CЈ or C leads to proteasomemediated Stat1 turnover and hence a subsequent block on the interferon-induced antiviral state, binding to the Y proteins does not destabilize Stat1, and the antiviral state can be observed (36,45). Our own work suggests that both CЈ and C expression but not Y is detrimental to cell viability.…”
Section: Y Protein Expression: Initiation Versus Proteolytic Processimentioning
confidence: 88%